Application of MATLAB software in the learning of the linear kinematics of a particle in university engineering students - Taipe, Ciro (2019)
The objective of this research was to determine the effectiveness of MATLAB software in the application of differential calculus in linear kinematics of a particle in engineering students of the National University of Juliaca, in order to optimize the academic performance of these students. The research design that has been assumed was the quasi-experimental. For the collection of information, the kinematic knowledge test of a particle has been used. The sample of the investigation has been conformed of the students of the second semester of Textile and Apparel Engineering. The results indicate that of 100% of the students in the experimental group, 9% is in the very good category, while in the control group 0% remains in the very good category.